2019
DOI: 10.1007/s12687-019-00450-7
|View full text |Cite
|
Sign up to set email alerts
|

Online BRCA1/2 screening in the Australian Jewish community: a qualitative study

Abstract: Screening programmes for BRCA1/2 Jewish Founder mutations (JFM) in the Jewish community have been advocated internationally. Implementation of these programmes could decrease morbidity and mortality of BRCA1/2 JFM carriers through the uptake of cancer screening strategies and risk-reducing surgery. An online programme offered to the Sydney Jewish community that delivers pre-test information and collects consent for BRCA1/2 JFM testing via a website is currently being evaluated (JeneScreen). Forty-three partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Israeli and Canadian Jewish population studies provided only 'pre-test information' and post-test genetic counselling for BRCA carriers, with >90% satisfaction rates [39,40]. An Australian Jewish population [41] and a UK general population study have demonstrated the feasibility of an online web-based decision aid (along with an optional telephone helpline) pre-test education and consent process [42].…”
Section: Discussionmentioning
confidence: 99%
“…Israeli and Canadian Jewish population studies provided only 'pre-test information' and post-test genetic counselling for BRCA carriers, with >90% satisfaction rates [39,40]. An Australian Jewish population [41] and a UK general population study have demonstrated the feasibility of an online web-based decision aid (along with an optional telephone helpline) pre-test education and consent process [42].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare funders and planners of genomic medicine services need to carefully consider the availability of access to genetic counselors before sequencing is introduced into routine clinical practice. Research shows patients are open to alternatives to traditional, face-to-face genetic counseling, such as group sessions or over the telephone [28,38], and recently through online platforms [39]. Such alternatives to face-to-face, individual sessions might offer a compromise between patients' desire for genetic counseling and the healthcare system's lack of resources to provide it.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A pilot UK study demonstrated feasibility of using a web-based decision aid and telephone helpline for population testing feasibility of this approach [78] and a recent AJ population study has also used an online pretest education and consent process. [79] Most studies opted to provide individual face-to-face post-test counselling for those with pathogenic mutations or very strong family histories. Rowley et al was the only study to not conduct this.…”
Section: What Type Of Genetic Counselling Is Appropriate For Pbgt?mentioning
confidence: 99%